Time course of the rubber hand illusion–induced analgesia - Benjamin Mosch; Xaver Fuchs; Theresia Tu; Martin Diers (PAIN Reports)
Abstract. Introduction:. Previous investigations on pain modulatory effects of the rubber hand illusion (RHI) yielded mixed results. However, these studies used separate stimuli to induce pain and the RHI. Using a visual-thermal stimulation approach, the illusion-inducing stimulus was simultaneously the pain stimulus which ensured that participants focused entirely on the illusion-inducing stimulus. Objectives:. In this study, we investigated the time course of pain modulation induced by illusionary body ownership over artificial hands using the visual-thermal RHI and the influence of the stimulation intensity. Methods:. In a 2 × 4 within-subject design, participants received thermal stimulation on their hidden real left hand, while the rubber hand synchronously lit up red. Four stimulation intensities were used: moderate pain (+0°C), −0.75°C, +0.75°C, and +1.5°C. For control trials, the rubber hand was rotated by 180°. With the right hand, participants provided continuous pain ratings using a slide knob. Results:. Embodiment ratings were higher in the RHI compared with the control condition. Continuous pain ratings were lower in the RHI condition for all temperature levels except for +0.75°C. Rubber hand illusion–induced pain reduction was observed throughout most of the stimulation interval, absent only at the very beginning and end. Conclusion:. These findings suggest that visual-thermal induction of the RHI is consistently associated with increased embodiment ratings, regardless of the temperature level presented. The illusion is further accompanied by reduced pain ratings throughout major parts of the stimulation interval. On the whole, these findings speak for the robustness of the effect and the practicality of our visual-thermal stimulation approach.